Approches interdisciplinaires en santé animale - Ducro, Christian; Fortané, Nicolas; Pau, Mathilde (éditions Quae, 2025)
Since the 2000s, the social sciences have been investing in animal health research. This book provides an overview of the interdisciplinary research conducted on this theme in the French-speaking research space, delivers a reflexive analysis, and identifies the challenges ahead. Based on case studies of various infectious animal diseases carried out in the North and South, the authors highlight social science research that sheds light on issues of interest to veterinary science, in particular practices, knowledge and forms of organisation relating to animal health. The book also presents work that has been co-constructed with stakeholders in the field as part of participatory research, with the aim of changing practices or improving surveillance and management systems. The place of interdisciplinary approaches in public action, training and expertise is examined and followed by a critical and reflective assessment of the dialogue between social sciences and veterinary science. This book is aimed at researchers and students in the humanities and social sciences, veterinary sciences and health, interested in interdisciplinary approaches.